Chitosan-vancomycin hydrogel incorporated bone repair scaffold based on staggered orthogonal structure: a viable dually controlled drug delivery system. Issue 6 (25th January 2023) - Gao, Xiaohan; Xu, Zexian; Li, Shangbo; Cheng, Lidi; Xu, Dian; Li, Li; Chen, Liqiang; Xu, Yaoxiang; Liu, Zijian; Liu, Yanshan; Sun, Jian
Abstract : The schematic diagram of preparing the composite scaffolds. Abstract : In clinical practice, challenges remain in the treatment of large infected bone defects. Bone tissue engineering scaffolds with good mechanical properties and antibiotic-controlled release are powerful strategies for infection treatment. In this study, we prepared polylactic acid (PLA)/nano-hydroxyapatite (nHA) scaffolds with vertical orthogonal and staggered orthogonal structures by applying 3D printing technology. In addition, vancomycin (Van)-based chitosan (CS) hydrogel (Gel@Van) was loaded on the scaffold (PLA/nHA/CS-Van) to form a local antibiotic release system. The microstructure of the composite scaffold had high porosity with interconnected three-dimensional networks. The mechanical properties of the PLA/nHA/CS-Van composite scaffold were enhanced by the addition of CS-Van. The results of the water contact angle analysis showed that the hydrophilicity of the drug-loaded scaffold improved. In addition, the composite scaffold could produce sustained release in vitro for more than 8 weeks without adverse effects on the proliferation and differentiation of mouse embryonic osteoblasts (MC3T3-E1), which confirmed its good biocompatibility. During the in vitro antimicrobial study, the composite scaffold effectively inhibited the growth of Staphylococcus aureus ( S. aureus ). Therefore, our results suggest that the PLA/nHA/CS-Van composite scaffold is a promising strategy for treating infected bone defects.